Neil Aggett: A man of the people - Reynolds, John (PINS-Psychology in Society, 2024)
Naidoo, Beverley (2012) Death of an idealist: In search of Neil Aggett. Johannesburg: Jonathan Ball. ISBN 978-1-86842-520-4 pbk. Pages xix + 475 Beverley Naidoo’s Death of an idealist: In search of Neil Aggett is an extraordinary achievement. She brings to life the complex dynamics that shaped this remarkable South African, and gives us a rich portrait not only of him as a multi-faceted and changing human being, but also of the social and political environment in which his short life was lived. She evokes the time in which Dr Neil Hudson Aggett lived in all its complexity, sketching vividly not only the horrors of the apartheid system and its security apparatuses, but also the complex socialisation of people living within that system. In her richly detailed account of Neil’s life, she illustrates the possibility of agency even in the most repressive of systems, and traces his development in dynamic interaction with his context.